Diverser a project of inclusive education from and for diversity - Soto, Jairo Eduardo; Mercado, Oris Maria; De la Hoz Reyes, Remberto (Technium Social Sciences Journal, 2021)
This article is a systematization of experiences related to inclusive education. From which the Universidad del Atlántico has been a leader in knowledge, promoting the development and transformation of the Caribbean region. Through a critical interpretation of this experience in its reconstruction, to understand the phenomenon, discover, and explain the logic of the process, the factors that have intervened in it, how they have related to each other and why they have done it in that way and not another. The systematizations of experiences involve a reflection on the practice, recapitulate what has been done, to relate it to other experiences or theoretical constructs that support or sustain it. It is a search for logic of meaning through the pertinent theorization with the developed actions. Once the results were obtained, a validation of them was conducted through a traffic light. For the indicators measured in the different scales (frequency, recognition, and existence), the percentage of people who had a favorable response was calculated and based on this percentage, the traffic light was obtained, achieving some results with which they triangle with the experiences conducted and the theoretical foundations. The scope of this research, established as a defined purpose for the educational community of the Universidad del Atlántico to take a critical approach to the experiences developed from an institutional project. Which accounts for learning that contributes to improving them, with the aim of contributing to a critical dialogue between the actors of educational processes?